IMPLEMENTATION OF THE SUPERVISION FUNCTIONS OF VILLAGES CONSULTANCY AGENCY IN OPTIMIZING VILLAGE DEVELOPMENT ACCORDING TO REGULATION OF THE MINISTER OF HOME AFFAIRS NUMBER 110 OF 2016 (Study at Lumbe, Nambo District, Banggai Regency) - Muhammad Rivai; 2Muh. Akbar,; Muhammad Yusuf Hasmin (Indonesian Research Journal in Legal Studies, 2023)
Implementation of the supervisory function of the Lumbe Village Consultative Body, Nambo District, Banggai Regency on the performance of the Lumbe village head which was carried out in a monitoring and evaluation manner and the results were not in accordance with the provisions of Article 46 paragraph (3) of the Minister of Home Affairs Regulation Number 110 of 2016 concerning Village Consultative Councils. So that it has not supported the administration of Lumbe village government to achieve legal goals. Several factors become obstacles, namely the limited human resources of BPD, low financing, low community culture and lack of BPD institutional facilities and infrastructure. Even so, there are supporting factors, namely harmonious coordination between the PBD and the village head and strong community support for the implementation of the supervisory function carried out by BPD Lumbe. It is recommended that the Ministry of Home Affairs issue guidelines for monitoring and evaluating the performance of village heads, strengthen support for BPDs and increase BPD budgets including increasing the availability of facilities and infrastructure for BPD Lumbe. Supervision functions are carried out effectively in supporting the implementation of village governance in a sustainable manner.